Determining mode I cohesive law of Pinus pinaster by coupling double cantilever beam test with digital image correlation (Fracture and Structural Integrity, 2014)
The direct identification of the cohesive law in pure mode I of Pinus pinaster is addressed. The approach couples the double cantilever beam (DCB) test with digital image correlation (DIC). Wooden beam specimens loaded in the radial-longitudinal (RL) fracture propagation system are used. The strain energy release rate in mode I (GI ) is uniquely determined from the load-displacement ( P ?? ) curve by means of the compliance-based beam method (CBBM). This method relies on the concept of equivalent elastic crack length ( eq a ) and therefore does not require the monitoring of crack propagation during test. The crack tip opening displacement in mode I ? ? I w is determined from the displacement field at the initial crack tip. The cohesive law in mode I I I (? ? w ) is then identified by numerical differentiation of the I I G ? w relationship. Moreover, the proposed procedure is validated by finite element analyses including cohesive zone modelling. It is concluded that the proposed data reduction scheme is adequate for assessing the cohesive law in pure mode I of P. pinaster.
Keywords: Wood